Safe and Predictable Hard Tissue Augmentation Modalities and Their Proper Use - ODA, Norimi; KUBOKI, Takuo; SONOYAMA, Wataru (Journal of Japanese Society of Oral Implantology, 2020)
To prevent recession of the marginal soft tissue after installation of the implant superstructure, a hard tissue thickness of 2 mm or more is required on the buccal (cheek) side of the implant. Therefore, if the remaining bone lacks thickness, some hard tissue augmentation is required.Conventionally, block bone grafting has been recommended for highly atrophied ridges. However, adaptation of the block bone to the recipient site, the surface morphology of which is usually irregular and complex, is problematic. This can lead to poor prognosis of the engraftment.Under these circumstances, Dr. Urban introduced "a sausage technique", in which a bone graft composed of a mixture of granular autogenous bone and slow-resorbing xenogenous bone (deproteinized bovine bone mineral) is covered and immobilized at the recipient site with a resorbable collagenous membrane that is secured using fixation pins. This technique allows high adaptability of the graft to the recipient site as it uses granular bone, and is relatively safe because it uses a resorbable membrane with a low wound dehiscence rate.However, large bone resorption, especially on the buccal (cheek) side of the alveolar ridge shoulder where the external pressure is markedly concentrated, is a major drawback and often requires additional GBR during implant placement. Moreover, the space-making capacity in the vertical direction is relatively poor.Therefore, in cases where a vertical and even horizontal hard tissue augmentation at the alveolar ridge shoulder is desired, a titanium-reinforced non-resorbable membrane is preferable.